Determinants of Deadwood-Inhabiting Fungal Communities in Temperate Forests: Molecular Evidence From a Large Scale Deadwood Decomposition Experiment - Purahong, Witoon; Wubet, Tesfaye; Lentendu, Guillaume; Hoppe, Björn; Jariyavidyanont, Katalee; Arnstadt, Tobias; Baber, Kristin; Otto, Peter; Kellner, Harald; Hofrichter, Martin; Bauhus, Jürgen; Weisser, Wolfgang W.; et al. (Frontiers in Microbiology, 2018)
Despite the important role of wood-inhabiting fungi (WIF) in deadwood decomposition, our knowledge of the factors shaping the dynamics of their species richness and community composition is scarce. This is due to limitations regarding the resolution of classical methods used for characterising WIF communities and to a lack of well-replicated experiments with sufficient numbers of tree species. Here, we used a large scale experiment with logs of 11 tree species at an early stage of decomposition, distributed across three regions of Germany, to identify the factors shaping WIF community composition and Operational Taxonomic Unit (OTU) richness using next generation sequencing. We found that tree species identity was the most significant factor, corresponding to (P < 0.001) and explaining 10% (representing 48% of the explainable variance) of the overall WIF community composition. The next important group of variables were wood-physicochemical properties, of which wood pH was the only factor that consistently corresponded to WIF community composition. For overall WIF richness patterns, we found that approximately 20% of the total variance was explained by wood N content, location, tree species identity and wood density. It is noteworthy that the importance of determinants of WIF community composition and richness appeared to depend greatly on tree type (broadleaved vs. coniferous) and it differed between the fungal phyla Ascomycota and Basidiomycota.